The use of wild vertebrates in contemporary Spanish ethnoveterinary medicine. (15th September 2016) - González, José A.; Amich, Francisco; Postigo-Mota, Salvador; Vallejo, José Ramón
Abstract: Ethnopharmacological relevance: This review documents the wide and varied repertoire of traditional practices based on the use of wild vertebrates in Spanish ethnoveterinary medicine (EVM) from the early 20th century to the present. Empirical practices, both ritual and magical, are recorded, and these EVM data are compared with those of other countries in the Mediterranean Region and Latin America. The data collected here could form a scientific foundation for future inventories of traditional knowledge and help in the discovery of new drugs for livestock. Materials and methods: A qualitative systematic review of international and national databases in the fields of ethnobiology, ethnoveterinary medicine, folklore and ethnography was made. Information was obtained from more than 60 documentary sources. Results: We recorded the use of 30 wild vertebrates and a total of 84 empirical remedies based on the use of a single species. The two most relevant zoological groups are reptiles and mammals. A wide diversity of body parts or products have been and are used. The meat and skin of snakes are the animal products most commonly used. These zootherapeutic resources have been and are used to treat or prevent ca. 50 animal diseases or conditions, in particular digestive and reproductive ailments, together with some infectious diseases. Sheep, cattle and equines form the group of domestic animals in which the greatest number of useful species are employed. In addition, many remedies and practices of the magical type are documented. In comparison with other culturally related areas, this is a rich heritage. Conclusions: Contemporary Spanish EVM practices amass a great richness of wild animal-based remedies. A diversity of animal parts or products have been used, offering a cultural heritage that could be a fundamental step in the discovery of new and low-cost drugs for treating livestock and alternative materials for pharmaceutical purposes. This overview contributes to the inventory of some uses and rituals seriously threatened by the progressive loss of local veterinary knowledge. Graphical abstract: